2022
DOI: 10.3389/fevo.2022.954232
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution of Landscape Patterns and Their Driving Forces Under Optimal Granularity and the Extent at the County and the Environmental Functional Regional Scales

Abstract: Research on the evolution and driving forces of landscape patterns can provide important support for ecological governance decision-making. However, the heterogeneity of landscape patterns at the microscale (grain size and extent) and the enforceability of the zoning scale at the macroscale deserve more attention. The optimal grain size (30 ×30 m) and the extent (500 m) for landscape pattern research were obtained by analyzing the fluctuation of landscape metrics and semivariogram models in this study. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The transfer matrix can reflect the area of land-use types in a single static period and aids the dynamic analysis of the flow direction of land-use type transfer, source of land-use transfer, and change amount (Nie et al, 2022). The raster calculator function in the ArcGIS10.2 software is used for processing, and Excel is used to calculate and output the final result.…”
Section: Land-use Transfer Matrixmentioning
confidence: 99%
“…The transfer matrix can reflect the area of land-use types in a single static period and aids the dynamic analysis of the flow direction of land-use type transfer, source of land-use transfer, and change amount (Nie et al, 2022). The raster calculator function in the ArcGIS10.2 software is used for processing, and Excel is used to calculate and output the final result.…”
Section: Land-use Transfer Matrixmentioning
confidence: 99%
“…During urban expansion phases, extensive tracts of natural landscapes, agricultural lands, and forests are invariably converted into urban built environments [3][4][5][6]. Such transformations engender increased fragmentation of the erstwhile cohesive landscape patterns [7,8], resulting in the subdivision of large, natural expanses into numerous smaller segments. This process not only elevates the quantity and density of landscape patches but also augments the complexity of landscape patterns [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al, found that there was a significant interaction enhancement effect between natural and social factors in influencing landscape fragmentation [61]. Nie et al, found the digital elevation model (DEM) and GDP to be the main drivers of landscape patterns using Geodetectors [8]. Therefore, in contrast to studies focusing solely on the influence of individual factors [64,65], research into the combined contributions of population, economic, and natural interactions to landscape patterns merits greater attention [66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the boundaries of rural landscapes' functional zones have been defined by administrative delineations or hand sketches [11]. However, the former approach makes it difficult to fully consider environmental factors, which may damage natural attributes [12], and limits the geospatial scale of the functional zones [13]. It will create a mismatch between functional zones and administrative zones, which will hinder the development of the region [14].…”
Section: Introductionmentioning
confidence: 99%